2010
DOI: 10.1001/archgenpsychiatry.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Etiological and Clinical Features of Childhood Psychotic Symptoms

Abstract: Context It has been reported that childhood psychotic symptoms are common in the general population and may signal neurodevelopmental processes that lead to schizophrenia. However, it is not clear whether these symptoms are associated with the same extensive risk factors established for adult schizophrenia. Objective To examine the construct validity of children’s self-reported psychotic symptoms by testing whether these symptoms share the risk factors and clinical features of adult schizophrenia. Design P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
246
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 220 publications
(270 citation statements)
references
References 92 publications
20
246
2
Order By: Relevance
“…The sample was drawn predominantly from deprived inner-city London (Laurens et al, 2007(Laurens et al, , 2008(Laurens et al, , 2012 and exceeds the prevalence of PLEs described in other pre-adolescent samples (range 6-17%, Poulton et al, 2000;Polanczyk et al, 2010;Wigman et al, 2011b). This elevated prevalence may relate to the demographics of this sample: the residing adult community has an elevated incidence of schizophrenia (Kirkbride et al, 2006) in addition to a self-reported PLE prevalence of 20% (Morgan et al, 2009).…”
Section: Prevalence Of Plesmentioning
confidence: 96%
See 1 more Smart Citation
“…The sample was drawn predominantly from deprived inner-city London (Laurens et al, 2007(Laurens et al, , 2008(Laurens et al, , 2012 and exceeds the prevalence of PLEs described in other pre-adolescent samples (range 6-17%, Poulton et al, 2000;Polanczyk et al, 2010;Wigman et al, 2011b). This elevated prevalence may relate to the demographics of this sample: the residing adult community has an elevated incidence of schizophrenia (Kirkbride et al, 2006) in addition to a self-reported PLE prevalence of 20% (Morgan et al, 2009).…”
Section: Prevalence Of Plesmentioning
confidence: 96%
“…Subclinical psychotic symptoms or psychotic-like experiences (PLEs) in childhood and adolescence are associated with concurrent emotional and behavioural difficulties (Laurens et al, 2007(Laurens et al, , 2012Nishida et al, 2008;Scott et al, 2009;Armando et al, 2010;Bartels-Velthuis et al, 2010;Polanczyk et al, 2010;Barragan et al, 2011;Kelleher et al, 2012b). PLEs that persist into adulthood increase risk for social dysfunction (Rossler et al, 2007), affective disturbance (van Rossum et al, 2011), substance misuse (Dhossche et al, 2002), and psychotic disorder .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have argued that work on this extended psychosis phenotype may provide valuable insights into the etiology of clinical psychotic disorder. 154,155 Neurocognitive research has only recently begun on this population but some of the cognitive differences that are characteristic of the prodrome and first-episode psychosis have already been shown to also occur in this population. In particular, deficits in processing speed have been found pronounced in this group.…”
Section: The Community Approachmentioning
confidence: 99%
“…More recently, evidence has been emerging that the clinical significance of psychotic symptoms extends beyond psychosis, with a number of research groups finding that young people who endorse questionnaire items on psychotic symptoms are also more likely to endorse symptoms of non-psychotic psychopathology, especially symptoms of depression (Hanssen et al, 2003, Johns et al, 2004, Kelleher et al, In Press, Nishida et al, 2008, Polanczyk et al, 2010, Scott et al, 2009b, Varghese et al, 2011, Wigman et al, 2011, Yung et al, 2009.…”
Section: Introductionmentioning
confidence: 99%